Factors Influencing Entrepreneurial Skills in Entrepreneurship Education: A Systematic Review - Syafrozi Haqi; Sukarsih, Sukarsih; Ahmad Happy Nashrullah; Andy Prasetyo Wati; Fulgentius Danardana Murwani (International journal of technology and education research, 2025)
This systematic review investigates the factors that influence the development of entrepreneurial skills in entrepreneurship education (EE). Recognizing the critical role of entrepreneurial skills in driving economic growth and innovation, as well as the increasing emphasis on CPD at different levels of education, this study synthesizes the existing literature to identify the key determinants of skills development. Using a rigorous methodology guided by the PRISMA framework, a comprehensive search was conducted on Google Scholar and Scopus, focusing on publications from 2020 to 2024 relevant to parental awareness and educational investment as proxies for broader influence factors. The meta-analysis method was strategically chosen to pinpoint significant variables and their interconnections. The initial identification phase yielded 478 records. Subsequent title and abstract screening yielded 378 potentially relevant records. Full-text retrieval was sought for these records, with 20 reports inaccessible. The remaining 200 full-text reports underwent a thorough eligibility assessment based on pre-defined criteria, which led to the exclusion of 130 reports for reasons such as language, incongruence with abstract content, or irrelevance to the specific topic of factors influencing entrepreneurial skills in PK. Ultimately, 70 studies met all inclusion criteria and were included in this systematic review. The findings of this synthesis provide a valuable understanding of the critical factors that shape the development of entrepreneurial skills in educational settings, offering insights for educators, policymakers, and future research efforts in improving the effectiveness of PK programs.